Localization of a site on bacterial superantigens that determines T cell receptor beta chain specificity (The Rockefeller University Press, 1993)
A defining characteristic of superantigens is their ability to stimulate T cells based predominantly on the type of variable segment of the T cell receptor (TCR) beta chain (V beta). The V beta specificity of these toxins most likely results from direct contact between the toxin and the TCR, although the low affinity nature of this binding has prevented direct assessment of this interaction. To identify important functional sites on the toxin, we created chimeric enterotoxin genes between staphylococcal enterotoxins A and E (SEA and SEE) and tested the V beta specificity of the chimeric toxins. This approach allowed us to identify three amino acid residues in the extreme COOH terminus of these toxins that are largely responsible for their ability to stimulate either human V beta 5- or V beta 8-bearing T cells, or mouse V beta 3 or V beta 11. We also found that residues in the NH2 terminus were required for wild-type levels of V beta-specific T cell activation, suggesting that the NH2 and COOH ends of these superantigens may come together to form the full TCR V beta contact site. SEA and SEE also differ with respect to their class II binding characteristics. Using the same chimeric molecules, we demonstrate that the first third of the molecule controls the class II binding phenotype. These data lead us to propose that for SEA and SEE, and perhaps for all bacterial-derived superantigens, the COOH and NH2 termini together form the contact sites for the TCR and therefore largely determine the V beta specificity of the toxin, while the NH2 terminus alone binds major histocompatibility complex class II molecules. The predominant role of the COOH terminus of bacterial superantigens in determining V beta specificity resembles current models being proposed for virally encoded superantigens, suggesting that these molecules may demonstrate some structural relationship not seen at the amino acid level.